Anticancer Activity of Kaempferol-3-O-β-D-(6″-coumaroyl)-Glucopyronoside from Euphorbia Hirta Flowers (Journal of Scientific Research, 2024)
Kaempferol-3-O-β-D- (6″-coumaroyl)-glucopyronoside flavonoid was extracted from the flower of Euphorbia Hirta. This compound was characterized by UV, 13C, and 1H NMR spectroscopy. The in-vitro anticancer study was performed using this flavonoid compound. Euphorbia Hirta flower showed good anticancer activity due to its higher content of flavonoids compound.